How urban noise can be influenced by the urban form - Oliveira, Marta Isabela Fernandes (2010)
The noise propagation is influenced by the behavior of the sound trajectory. The temperatures, the wind, the type of soil are other elements that influence the noise propagation. But the mainly causer of trajectory alterations are the barriers or the urban obstacles. Therefore the study will allow monitoring the interaction of noise propagation effects in the studied urban forms. Using urban indicators and a noise prediction model is possible to associated noise categories to urban façades forms. The effects of noise in façades can be minimized in advance with the creation of different scenarios and foresee in a preliminary phase the most exposed façade to a higher noise level.